Islamization In Southeast Asia: History And Development In Southeast Asian Countries - Rosyad Syahidin; Muhammad Abdi Darmawan; Syahrul Anwar (Yayasan Cendekia Gagayunan Indonesia, 2024)
Islam is a rapidly growing religion in Southeast Asia, spreading through trade, proselytization, marriage, and cultural assimilation. This study aims to examine the history of Islam’s arrival in the region, its development across various ASEAN countries, and the differing conditions faced by Muslims in each nation. Using a qualitative approach through literature review, it was found that Islam first entered Southeast Asia in the 7th century CE via Arab, Persian, and Indian traders. Indonesia, as the initial center for the spread of Islam, became the country with the largest Muslim population in the region, followed by Malaysia and Brunei Darussalam. However, the development of Islam in countries like Thailand, the Philippines, and Myanmar has faced significant challenges due to political conflicts, cultural differences, and discrimination against Muslim minorities. In addition to trade and marriage, methods of proselytization such as education, art, and Sufism also played a crucial role in the process of Islamization. This study highlights the differing social and political dynamics influencing the application of Islamic law and the lives of Muslims in each Southeast Asian country. Consequently, this research provides an in-depth understanding of the history and development of Islam and its role in shaping the region's identity.